Advances in CaV1.1 gating: New insights into permeation and voltage-sensing mechanisms - Hugo Bibollet; Audra Kramer; Roger A. Bannister; Erick O. Hernández-Ochoa (Taylor & Francis Group, 2023)
ABSTRACTThe CaV1.1 voltage-gated Ca2+ channel carries L-type Ca2+ current and is the voltage-sensor for excitation-contraction (EC) coupling in skeletal muscle. Significant breakthroughs in the EC coupling field have often been close on the heels of technological advancement. In particular, CaV1.1 was the first voltage-gated Ca2+ channel to be cloned, the first ion channel to have its gating current measured and the first ion channel to have an effectively null animal model. Though these innovations have provided invaluable information regarding how CaV1.1 detects changes in membrane potential and transmits intra- and inter-molecular signals which cause opening of the channel pore and support Ca2+ release from the sarcoplasmic reticulum remain elusive. Here, we review current perspectives on this topic including the recent application of functional site-directed fluorometry.